2010
DOI: 10.1037/a0020268
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of public/private health care insurance parameters for independent psychological practice.

Abstract: Managed care cost-cutting strategies are more prevalent in the private (employer provided) than public (Medicare/Medicaid) health care sectors. The main organizational managed care strategy pertaining to the independent practice of psychology has been the separation of the administration of mental from medical health care though behavioral health carve-outs. These organizations typically offer lower reimbursement rates and have greater preauthorization requirements than non-managed care public plans for the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…If the clinician does not follow the DSM criteria based on youth or parent reports of symptoms, other factors must influence the clinical diagnosis. Possible extraneous influences include: a) group dynamics in the Demonstration treatment teams; b) treatment options, which differed between the Demonstration and Comparison sites; c) reimbursement policies; and d) social desirability (Gasquoine, 2010;Gibelman & Mason, 2002;Mullins-Sweatt & Widiger, 2009;Newell & Saltzman, 1995;Rost et al, 1994;Setterberg et al, 1991). In a survey of 460 child psychiatrists, 55% reported using adjustment disorder diagnoses to avoid more stigmatizing diagnoses (Setterberg et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…If the clinician does not follow the DSM criteria based on youth or parent reports of symptoms, other factors must influence the clinical diagnosis. Possible extraneous influences include: a) group dynamics in the Demonstration treatment teams; b) treatment options, which differed between the Demonstration and Comparison sites; c) reimbursement policies; and d) social desirability (Gasquoine, 2010;Gibelman & Mason, 2002;Mullins-Sweatt & Widiger, 2009;Newell & Saltzman, 1995;Rost et al, 1994;Setterberg et al, 1991). In a survey of 460 child psychiatrists, 55% reported using adjustment disorder diagnoses to avoid more stigmatizing diagnoses (Setterberg et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…If the clinician does not follow the DSM criteria based on youth or parent reports of symptoms, other factors must influence the clinical diagnosis. Possible extraneous influences include: a) group dynamics in the Demonstration treatment teams; b) treatment options, which differed between the Demonstration and Comparison sites; c) reimbursement policies; and d) social desirability (Gasquoine, 2010;Gibelman & Mason, 2002;MullinsSweatt & Widiger, 2009;Newell & Saltzman, 1995;Rost et al, 1994;Setterberg et al, 1991). In a survey of 460 child psychiatrists, 55% reported using adjustment disorder diagnoses to avoid more stigmatizing diagnoses (Setterberg et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there is the relatively hidden world of the effect of third party reimbursement and stigma on diagnosis determination. Given that the diagnosis assigned to the client is sometimes critical to whether or not payment will be authorized for the delivery of treatment, and that payment is often dependent on a diagnosis for which treatment is deemed "medically necessary" (Eriksen & Kress, 2005;McNally, 2011), it is not surprising that preliminary evidence has accumulated that suggests reimbursement schemes affect diagnosis (Gasquoine, 2010;Gibelman & Mason, 2002;Jensen-Doss & Hawley, 2011;Lowe, Pomerantz, & Pettibone, 2007). However, this potential bias has not been investigated with children and adolescents.…”
Section: Bias In Assigning Formal Diagnosis Based On Informantmentioning
confidence: 99%
“…Private insurance fees have historically dropped, especially since managed health care grew in the 1970s, whereas public sector fees either grew or remained unchanged (Gasquoine, 2010;Nordal, 2012). Comparison of reimbursement rates showed that Medicare and even Medicaid rates have almost always surpassed those of private managed care companies (Gasquoine, 2010). (In addition to the financial advantages of the public sector, there have been administrative advantages in terms of no preauthorization requirements, no utilization review procedures, and no gatekeeping restrictions.)…”
Section: Advocacymentioning
confidence: 99%